2017
DOI: 10.1017/s1478951517000943
|View full text |Cite
|
Sign up to set email alerts
|

Medical students’ attitudes towards participating in a palliative medicine course: A new specialty in Israel

Abstract: The overall satisfaction of the 45 students was high. The most contributory parts of the course were the multidisciplinary team and the complementary and alternative medicine. Participating in the staff meetings and accompanying physicians in their daily work were scored as the least contributory parts.Significance of resultsThis preliminary study demonstrated students' overall high satisfaction with the newly established palliative care course and their need for more practical skills. Future studies should in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…A clear change regarding PC education can be observed. The increasing acceptance of PC education is reflected in the students’ feedback (Bar-Sela et al, 2017). In general, there is a new generation of students who are more open to PC philosophy and reflection.…”
Section: Discussionmentioning
confidence: 99%
“…A clear change regarding PC education can be observed. The increasing acceptance of PC education is reflected in the students’ feedback (Bar-Sela et al, 2017). In general, there is a new generation of students who are more open to PC philosophy and reflection.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from different countries have reported that medical students from United States (12), Brazil (13), Germany (14) and Turkey (15) have gaps in education and PC training (16,17) and reported uncertain providing it (18).…”
Section: Discussionmentioning
confidence: 99%
“…According to this law, patients are defined as terminally ill if they are suffering from an incurable disease and have a life expectancy of up to 6 months. Although attention to palliative care in general, and advance care planning in particular, has developed over recent years in Israel (20)(21)(22), >1% of the adult population has formally completed advance directives or signed a durable power of attorney (23).…”
Section: Advance Care Planning In Israelmentioning
confidence: 99%